Neo-colonialism in Our Schools: Representations of Indigenous Perspectives in Ontario Science Curricula - Kim, Eun-Ji (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
Motivated by the striking under-representation of Indigenous students in the field of science and technology, the Ontario Ministry of Education has attempted to integrate Aboriginal perspectives into their official curricula in hopes of making a more culturally relevant curriculum for Indigenous students. Using hermeneutic content analysis (HCA), a mixed-method framework for analyzing content, this study examined how and to what extent Aboriginal content is represented in Ontario’s official science curriculum documents. Given that very little has been published in this specific area, this research sheds light on the current state of the representation of Aboriginal cultures in contemporary Canadian science curriculum.